Shaping The Future Of Business In Social Media (Trinity Journal of Management, IT & Media (TJMITM), 2014)
A new trend of social media is shaping the future of business  environment according to its operations. It has also helped businesses to  increase their worthiness, cultivate strategic partnerships and increase  their contact with customers and suppliers. It has become important for  business owners and marketers to understand how social media works  as a communication and marketing tool. The study focused on  establishing the effect of social media on the growth of SMEs in Bihar.  The study used descriptive research design. Questionnaires were  administered on 206 SMEs in Bihar, with the respondents being either  the owners or managers. Cluster sampling was used to divide the  population of interest and then simple random probability sampling  technique was used to further identify the specific businesses to be used  for the study. Both quantitative and qualitative data was collected and  then analyzed using SPSS. The study established that social media tools  offer greater market accessibility and CRM, which in turn have a  significant impact on the growth of SMEs. It revealed that geographical  barriers can be broken down by the use of social media tools.
Keywords: Social Media; Customer Relationship Management; Entrepreneurship